Pengembangan Media Bigbook Cerita Rakyat untuk Meningkatkan Empati dan Kemampuan Bercerita Anak Usia Dini - Dheasari, Agustiarini Eka (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2020)
The purpose of this research is to develop bigbook folklore media to improve the empathy and storytelling ability of early childhood, especially age 5-6 years. This research is research and development (R&D) using ADDIE development model (Analyze, Design, Develop, Implementation, and Evaluate). Collecting data used interview guides, validation, observation sheets and teacher questionnaires. Data analysis techniques in this study used Independent t-test with a significance level of 0.05. Based on the results of the assessment experts showed that the product developed "very good". This shows that the bigbook media is appropriate to be used to increase empathy and storytelling skills of children aged 5-6 years. Based on the results of the study, there was a difference improvement of storytelling and empathy skills in the final outcomes between post treatment of the control group without bigbook media and post treatment of experimental group using bigbook media. The sig (2-tailed) value of the storytelling is 0,000 (very good) and empathy children received a sig (2-tailed) value of 0,000 (very good). The result of this study that the bigbook media based on folklore is effectively used to increase empathy and storytelling skills of children aged 5-6 years.